Accounting for Exchange Rate Fluctuations. - Shwayder, Keith R. (The Accounting Review, 1972)
Abstract The article focuses on a proposal for the accounting measurement and/or the measurement of foreign exchange exposure for a domestic parent with foreign subsidiaries. The proposed method differs from other recommendations in the accounting literature in the explicit treatment of fluctuations in the domestic price level, the foreign price level, and the exchange rate. In the other methods examined, there were difficulties in accounting for at least one of those changes. Such separate treatment of each factor results in an economic and an accounting model which is viable–not only under today's international monetary environment–but which should also hold true under other international monetary arrangements. As a measure of exposure, the proposed method assists in hedging decisions. When incorporated in the financial statements, the proposed method assists in intercompany comparisons by effectively measuring the economic effects of price and exchange-rate movements. Finally, as indicated in the last section, the approach can be extended beyond the simplifying assumptions used in the article.